Pengaruh Motivasi, Pelatihan Pajakku, Brevet Ab Terhadap Minat Mahasiswa Jurusan Akuntansi Untuk Berkarier Di Bidang Perpajakan: Studi Kasus Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi Bisnis dan Pariwisata Universitas Hindu Indonesia - Ni Made Rya Ryani Tresiana; Ni Komang Sumadi Tresiana; Ni Putu Trisna Windika Pratiwi Tresiana (UNHI Press, 2026)
This study addresses the issue of low interest among accounting students in pursuing careers in taxation, even though the demand for tax professionals in Indonesia, particularly in Bali, continues to rise due to increasingly complex regulations and the rapid development of the tourism and service industries. The purpose of this study is to analyze the impact of motivation, Taxku training, and AB Brevet certification on students’ interest in building a career in taxation within the Accounting Study Program, Faculty of Economics, Business, and Tourism, Hindu University of Indonesia. This research adopts a quantitative approach, involving 177 students from the 2021-2022 cohorts selected through a saturated sampling method. Data were collected through a Likert-scale questionnaire administered via Google Forms and analyzed using multiple linear regression with SPSS after passing validity, reliability,and classical assumption tests. The findings reveal that all three variablesmotivation, Taxku training, and AB Brevet certification have a positive and statistically significant influence on students’ interest in pursuing a taxation career. These results highlight the importance of strengthening institutional support through the expansion of taxation training programs and certification access to improve students’ motivation and professional readiness in the field of taxation.